Factors Influencing the Improvement of BPJS Ketenagakerjaan Product Inclusivity in Medan City - Elna Sari Nasution; Atika Atika; Aqwa Naser Daulay (MASI Mandiri Edukasi, 2025)
This study aims to analyze the influence of public literacy, program socialization, service quality, and facility accessibility on the enhancement of the inclusivity of BPJS Employment products in Medan City. The research employs a quantitative approach with associative analysis to examine the relationships among variables both simultaneously and partially. The research objects include participants and potential participants of BPJS Employment in Medan City, covering both formal and informal sectors. The sample consisted of 100 respondents determined through a random sampling technique. Data were collected using structured questionnaires distributed directly to the respondents. The results indicate that public literacy, program socialization, service quality, and facility accessibility have a positive and significant effect, both partially and simultaneously, on the inclusivity of BPJS Employment products. These findings suggest that higher levels of public literacy, more effective program socialization, better service quality, and easier access to facilities contribute to the improvement of BPJS Employment product inclusivity in Medan City. Therefore, an integrative and sustainable approach to these four factors serves as an essential strategy for expanding public participation in the national labor protection program.